Comments on author citations for nomenclatural novelties published in volume 15 of the Flora Reipublicae Popularis Sinicae (FRPS) - Peng, Yu-Lan; Zhang, Li-Bing (Phytotaxa, 2016)
Zhu (2015) stated that “the correct author citation for nomenclatural novelties in volume 15 of Flora Reipublicae Popularis Sinicae (Wang & Tang 1978) was not adequately explained in the publication”. He then used the information provided in Chen et al. (1993) as external evidence and applied Art. 46.9 of the Melbourne Code (McNeill et al. 2012) to reconsider the authorship citations of the 11 species and one variety. Thus, he (Zhu 2015) suggested to add an “ex” citation of the individual contributors after the original authors “Wang & Tang [Fa-Tsuan Wang (1899–1985) & Tsin Tang (1897–1984)]”.